Perancangan Kerangka Kerja Togaf Untuk Mendukung Pengembangan Sistem Informasi Produksi PT. XYZ - Anggun Fergina; Irfan Dwiguna Sumitra (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2020)
PT XYZ is a textile company located in Cimahi City with a focus on producing fabrics to be used as suits and clothes. In processing production, and recording production results to improve business processes, PT XYZ is assisted by using an information system to reduce input errors and can be integrated between divisions in the production process. TIASA is an information system to support and bridge the company's internal business processes with the SAP information system. TIASA has a goal in several menu features that suit the company's business processes, from human resources to production processes. Based on the problems in TIASA information systems, especially in the production section, it is necessary to develop a production information system for PT XYZ using the TOGAF architecture development method (ADM) to integrate several parts of the production process. Based on the research results, the togaf framework design to support the development of PT XYZ's production information system using the togaf architecture development method (ADM) can provide blueprint guidelines and documentation for future developments. In this model, includes the scope of data architecture, application architecture, and technology architecture as an enterprise architectural design. Index Terms—Togaf, Architecture Development Method, enterprise architecture planning, textile, production, blueprints.